2023
DOI: 10.1186/s40793-023-00518-5
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary patterns of archaea predominant in acidic environment

Abstract: Background Archaea of the order Thermoplasmatales are widely distributed in natural acidic areas and are amongst the most acidophilic prokaryotic organisms known so far. These organisms are difficult to culture, with currently only six genera validly published since the discovery of Thermoplasma acidophilum in 1970. Moreover, known great diversity of uncultured Thermoplasmatales represents microbial dark matter and underlines the necessity of efforts in cultivation and study of these archaea. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 75 publications
0
1
0
Order By: Relevance
“…It was shown that these archaea are probably not iron oxidizers and cannot play a key role in sulfide mineral oxidation. At the same time, archaea belonging to the group of E-plasma possessed genes involved in both iron and sulfur oxidation (sulfocyanin and heterodisulfide reductase) [92].…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that these archaea are probably not iron oxidizers and cannot play a key role in sulfide mineral oxidation. At the same time, archaea belonging to the group of E-plasma possessed genes involved in both iron and sulfur oxidation (sulfocyanin and heterodisulfide reductase) [92].…”
Section: Discussionmentioning
confidence: 99%